(untitled) (Economics and region, 2016)
The authors distinguished the institutional grounds of energetic service contract (ESC). It is described that the main demand for substance and structure of ESC is a list of steps which are influential for energetic economy and energetic effectiveness’ increasing. It was given a procedure of effectiveness valuation through realization of economy steps. The authors noted that the primary condition in this case is valuation of economy measure as naturally as also financially. It is substantiated that very important for real valuation of economy measures is methodological base of fixing and verification of energetic effectiveness. It is confirmed that institute of ESC is a form of partnering between state and private sector of economics which based on the co-operation of private and public partners. So energetic service activity is as consolidative section which includes different interests of many representatives of modern economic system, there are: state, makers of energetic saving equipments, financial institutes, business etc.